PENGARUH KUALITAS SUMBER DAYA MANUSIA TERHADAP PENINGKATAN LAYANAN ADMINISTRASI KEPEGAWAIAN PADA BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA DAERAH KOTA TOMOHON - Chintia Silvana Pomantow; Fakhruddin Kurnia M (PIRSAP (Paser Institute for Scientific Research and Publications), 2024)
This research was carried out at the Tomohon City Regional Personnel and Human Resources Development Agency. The quality of human resources (HR) has become the main focus for many organizations, including the Human Resources and Personnel Development Agency (BKPSDM), because the quality of HR is the main determinant of the efficiency and effectiveness of personnel administration services. This research aims to examine the relationship between the quality of human resources and improving personnel administration services at BKPSDM. The method used is quantitative research using survey techniques via distributed questionnaires as a data collection tool. The sample for this research is BKPSDM employees themselves and related parties who have experience in the personnel administration service process. From the results of the research conducted, it was found that the administrative service process at the Tomohon City Regional Personnel and Human Resources Development Agency was not optimal. For these reasons, the author is interested in conducting research with the title